Implementation of interactive home automation systems based on email and Bluetooth technologies - Sunehra, Dhiraj; Veena, M. (2015 International Conference on Information Processing (ICIP), 2015)
Automation systems are gaining lot of popularity nowadays and are being used at various places such as shopping malls, toll gates, airports, etc. In this paper, we present the implementation details of two schemes for home automation and control. The first scheme presents a prototype of Home Automation System (HAS) for remotely controlling the appliances at home through the subject of e-mail. This system is based on ARM11 Raspberry Pi microcontroller board. Python Integrated Development Environment (IDE) is used for developing the necessary software. The second scheme uses Bluetooth technology for controlling the devices when we are at home. It uses a HC-05 Bluetooth module and Bluetooth Controller mobile application for switching on or off the appliances. Relays and LEDs are used as load to demonstrate the working of the system. This prototype design can be extended for several applications including surveillance, power monitoring, fault monitoring, power control and security.